2020
DOI: 10.1177/2472555220926920
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Meets Zebrafish: Accelerating the Discovery of New Therapeutic Targets

Abstract: Bringing a new drug to the market costs an average of US$2.6 billion and takes more than 10 years from discovery to regulatory approval. Despite the need to reduce cost and time to increase productivity, pharma companies tend to crowd their efforts in the same indications and drug targets. This results in the commercialization of drugs that share the same mechanism of action (MoA) and, in many cases, equivalent efficacies among them—an outcome that helps neither patients nor the balance sheet of the companies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 137 publications
0
12
0
Order By: Relevance
“…Only a limited number of studies to date have used novel targeted-mutagenesis techniques such as CRISPR/Cas9 to generate target discovery studies in the neuroscience field. However, it is expected that a growing number of studies will be reported soon ( Rubbini et al, 2020 ) as shown by the example of target identification in a C3orf70 knockout zebrafish mutants with impaired circadian rhythm and altered light-dark neurobehaviors ( Ashikawa et al, 2019 ) in which the C3orf70 gene was reported to be a shared target of Neurog1/2 and Asc11 . As a result, C3orf70 mutations may be linked to neurodevelopmental and neuropsychiatric diseases in these brain locations and could be exploited as a therapeutic target ( Ashikawa et al, 2019 ).…”
Section: Using Zebrafish To Accelerate Drug Discoverymentioning
confidence: 99%
“…Only a limited number of studies to date have used novel targeted-mutagenesis techniques such as CRISPR/Cas9 to generate target discovery studies in the neuroscience field. However, it is expected that a growing number of studies will be reported soon ( Rubbini et al, 2020 ) as shown by the example of target identification in a C3orf70 knockout zebrafish mutants with impaired circadian rhythm and altered light-dark neurobehaviors ( Ashikawa et al, 2019 ) in which the C3orf70 gene was reported to be a shared target of Neurog1/2 and Asc11 . As a result, C3orf70 mutations may be linked to neurodevelopmental and neuropsychiatric diseases in these brain locations and could be exploited as a therapeutic target ( Ashikawa et al, 2019 ).…”
Section: Using Zebrafish To Accelerate Drug Discoverymentioning
confidence: 99%
“…While several reports have shown successful utilization of CRISPR technology in primary fibroblasts from different origins, 6 to our knowledge this work describes the first whole genome-wide arrayed CRISPR screen in such a model. The perspective from Rubbini et al 7 highlights how the zebrafish model might represent an attractive solution for functional genomics studies in in vivo models that allow the retention of some level of throughput. One of the key advantages of the use of zebrafish in target discovery is the availability of well-characterized phenotypic readouts related to several human diseases (including neurological disorders, inflammation, cancer, and cardiovascular disease) at a fraction of the cost compared with other animal models.…”
Section: Translatable Modelsmentioning
confidence: 99%
“…The CRISPR-Cas system is a prokaryotic adaptive immune system against viruses present in various archaea and bacteria [3]. CRISPR has advanced our understanding of fundamental biological processes and aided in the discovery of new disease targets [4][5][6][7]. By leveraging its ability to identify and cut with single nucleotide precision, many applications have been derived.…”
Section: Introductionmentioning
confidence: 99%